2012
DOI: 10.1099/ijs.0.032367-0
|View full text |Cite
|
Sign up to set email alerts
|

Leuconostoc miyukkimchii sp. nov., isolated from brown algae (Undaria pinnatifida) kimchi

Abstract: A Gram-staining-positive, non-motile and non-spore-forming lactic acid bacterium, designated strain M2 T , was isolated from fermented brown algae (Undaria pinnatifida) kimchi in South Korea. Cells of the isolate were facultatively anaerobic ovoids and showed catalase-and oxidasenegative reactions. Growth of strain M2 T was observed at 4-35 6C and at pH 5.0-9.0. The G+C content of the genomic DNA was 42.5 mol%. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain M2 T belonged to the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Indeed, the genus Leuconostoc was revised in the last years with the description of novel species and subspecies, such as L . myukkimchi [ 61 ], L . mesenteroides subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the genus Leuconostoc was revised in the last years with the description of novel species and subspecies, such as L . myukkimchi [ 61 ], L . mesenteroides subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, L. argentinum has been reclassified as a synonym of L. lactis following numerical analysis of repetitive extragenic palindromic-PCR patterns, whole-cell protein profiles (SDS-PAGE) and fluorescent amplified fragment length polymorphism (FAFLP) band patterns [11]. New species, including L. holzapfelii, L. palmae and L. miyukkimchii , have also been identified from wine and kimchi [12-14]. …”
Section: Introductionmentioning
confidence: 99%
“…Taxonomic studies using conventional and molecular methods have shown that various lactic acid bacterium (LAB) species, such as Leuconostoc mesenteroides, Lactobacillus sakei, and Weissella koreensis, are likely to be key players responsible for kimchi fermentation (1,6,9). Members of the genus Leuconostoc are heterofermentative LAB species that are typically dominant during the early and mid-phases of kimchi fermentation (2,6) and are known to be among the LAB species that determine kimchi's flavors (7,10,12).…”
mentioning
confidence: 99%